1996
DOI: 10.1080/15216549600201852
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of polyadenylic acid (5′) with histone H1 or protamine

Abstract: The interaction between polyadenylic acid (5′) (poly[A]) and histone (or protamine) was analyzed by electrophoretic retardation of poly[A]‐histone (or protamine) complex in agarose gel. The potency of interaction was protamine > histone H1, arginine‐rich histone > other histones. The catalytic subunit of cyclic AMP‐dependent protein kinase effectively decreased the electrophoretic retardation of poly[A]‐histone H1. The interaction between poly[A] and histone H1 was also detected by the drastically enhanced abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It has been reported that NO was of ubiquitous occurrence in higher plants, including foliage, intact seeds, individual seed components and in roots [38][39][40]. The interplay between NO and ethylene in the regulation of maturation and senescence of plant tissue has been already evidenced [41].…”
Section: Hydrophytes Samples Analysismentioning
confidence: 99%
“…It has been reported that NO was of ubiquitous occurrence in higher plants, including foliage, intact seeds, individual seed components and in roots [38][39][40]. The interplay between NO and ethylene in the regulation of maturation and senescence of plant tissue has been already evidenced [41].…”
Section: Hydrophytes Samples Analysismentioning
confidence: 99%
“…NOS-like activity has been reported to be present in plant chloroplasts and peroxysomes (3,50). Mouse anti-NOS antibodies recognized NOS, or a NOS-like molecule, in peas, wheat, and corn (35,51,55). Ninneman and Maier (48) observed notable levels citrulline formation in higher plants, and also demonstrated NOS activity in plants by employing inhibitors such as L-NNA (NG-nitro-L-arginine) and L-NAME (NW-nitro-L-arginine methyl ester).…”
Section: Biosynthesis Of Nitric Oxidementioning
confidence: 99%